Keberhasilan Usaha Berbasis Motivasi Anggota, Komitmen Organisasi, melalui Partisipasi Anggota - Dwi Gemina; Tini Kartini; Luki Adiyanto (Pusat Riset dan Inovasi Nasional, 2025)
Cooperatives serve as a people-based economic institution that plays a strategic role in efforts to improve social welfare, especially for their members. This study aims to analyze the direct, indirect, and total influence of motivation and commitment on business success at KPRI Usaha Sekerja BBLITVET Bogor, with member participation as an intervening variable. The population in this study includes all members of KPRI Usaha Sekerja BBLITVET Bogor, totaling 130 people. The sampling technique used is saturated sampling, in which all members of the population were used as research samples. The type of data used is ordinal data, which was then converted into metric data on an interval scale using the Method of Successive Interval (MSI) method. The data analysis techniques in this study include descriptive analysis, verification analysis, path analysis, and the Sobel test to examine the role of the intervening variable. The research instrument in the form of a questionnaire has been tested for validity, reliability, and met the classical assumption tests. The results of the study show that motivation and commitment have a direct and positive influence on business success. In addition, motivation, commitment, and member participation also directly have a positive influence on business success. Furthermore, motivation and commitment also indirectly influence business success through the active participation of cooperative members.